Multifunctional nanogels via self - assembly of polymers - Aktan, Buğra. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Water soluble multifunctional nano structures are promising candidates as imaging agents for early and post-treatment diagnostics. In this thesis, design and synthesis of novel multifunctional nanogels have been achieved by chemically crosslinking nanogels obtained via polymer self-assembly. A poly(ethylene glycol)methacrylate (PEGMA) based maleimide bearing polymer was synthesized via atom transfer radical polymerization (ATRP). In particular, a PEGMA containing amphiphilic copolymer was used to synthesize the nanogels due to its lower critical solubility temperature (LCST) behavior. These polymers form nano-size aggregates in aqueous solutions upon heating. Due to the presence of thiol-reactive maleimide units on these polymers they can be crosslinked via thiol bearing crosslinkers to obtain nanogels. After gelation, functionalization of residual maleimide groups in the nanogels are available for conjugation of imaging agents, as shown via addition of a thiol bearing fluorescent dye (BODIPY-SH). In addition, to demonstrate multifunctionality of nanogels, thiol bearing cyclic peptide based targeting group, cRGDfC, and maleimide bearing dye N-(fluoresceinyl) maleimide were sequentially conjugated to nanogels under mild conditions. Parent nanogels did not show any in vitro toxicity on cancerous breast cell lines. Presence of the targeting group on the nanogels increased the internalization of nanogels into the cancerous breast cell lines as deduced from fluorescence microscopy and flow cytometry studies. Overall, facile synthesis of a multifunctional nanogel that can serve as a promising candidate in the field of diagnostics was achieved.
Keywords: Nanogels.; Biomedical materials.